(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The sample size of 384 was calculated assuming theprevalence of malnutrition was 50%, with relative precision of 10% at 95%confidence. For this study, 3 slums (Faltuganj, Kurramgotia and Kalibadi) wererandomly selected from the urban area. All children aged 5-15 years from eachof these slums were examined. A total of 512 children (297 boys and 215 girls)were interviewed and examined. A pre-designed and pre-tested questionnaire wasused to interview the study participants to elicit information on family characteristicslike residence, religion, type of family, education and occupation of parents;and information on individual characteristics like age, sex and eating habits.Anthropometric measurements were taken and noted by trained field workers. Thequestionnaire was pre-tested on 5 children from each slums. Necessarymodifications were made in the questionnaire before the start of the study.Ethical approval was obtained from Institute of Medical Sciences, Haryana. Forparticipation of the study subjects parents/guardians/caregivers were informedabout the study objectives and gave informed written consent prior to inclusioninto the study.